2013
DOI: 10.1007/s10551-013-1978-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Attitudinal and Organisational Variables on Workplace Environmentally Friendly Behaviours

Abstract: Further information on publisher's website:http://dx.doi.org/10.1007/s10551- 013-1978-6 Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/s10551-013-1978-6.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 68 publications
0
93
0
Order By: Relevance
“…Individual factors which have been studied include attitudes and beliefs (Jones, 2010;Chun, Shin, Choi & Kim, 2013;Manika, Wells, Gregory-Smith & Gentry, 2014), norms (Scherbaum, Popovich & Finlinson, 2008;Carrico & Riemer, 2011), self-efficacy (Smith & O'Sullivan, 2012), habit (Siero et al, 1996), motivation (Lee, De Young & Marans, 1995;Tudor, Barr & Gilg, 2008), knowledge (Siero et al, 1984) and socio-demographics (Wehrmeyer & McNeil, 2000). The most comprehensive study of employee environmental behaviour within the tourism literature focused on individual (individual environmental beliefs, personal environmental norms, self-reported environmental behaviour) and organisational variables (green organisational climate) as well as demographics to explain employee behaviour (Chou, 2014).…”
Section: Employee Environmental Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Individual factors which have been studied include attitudes and beliefs (Jones, 2010;Chun, Shin, Choi & Kim, 2013;Manika, Wells, Gregory-Smith & Gentry, 2014), norms (Scherbaum, Popovich & Finlinson, 2008;Carrico & Riemer, 2011), self-efficacy (Smith & O'Sullivan, 2012), habit (Siero et al, 1996), motivation (Lee, De Young & Marans, 1995;Tudor, Barr & Gilg, 2008), knowledge (Siero et al, 1984) and socio-demographics (Wehrmeyer & McNeil, 2000). The most comprehensive study of employee environmental behaviour within the tourism literature focused on individual (individual environmental beliefs, personal environmental norms, self-reported environmental behaviour) and organisational variables (green organisational climate) as well as demographics to explain employee behaviour (Chou, 2014).…”
Section: Employee Environmental Behaviourmentioning
confidence: 99%
“…Gregory-Smith, Wells, Manika and Graham (in press) found that employees' satisfaction with the 11 level of impact on the environment are negatively correlated with general environmentally friendly attitudes, noting that those who have stronger environmental attitudes, consider that they have a stronger negative impact on the environment and thus, are less satisfied with their level of impact on the environment. In addition, research suggests that if employees have strong pro-environmental attitudes they will report higher levels of pro-environmental behaviour (Manika et al, 2014).…”
Section: Perceived Current Satisfaction With Environmental Behaviourmentioning
confidence: 99%
See 3 more Smart Citations